Patchworked creative practice and mobile ecologies - Venter, Marija Anja (Centre for Film and Media Studies, 2018)
As the use of mobile technologies, consumer electronics and the internet expand, there are more opportunities for young visual designers around the world to gain access to design industries. Yet differences in infrastructure and spatial configurations create distinct obstacles and opportunities for emerging designers from marginal contexts, as often these infrastructures are not designed with them in mind. Employing a practice perspective, which brings together concerns around identity and infrastructure, I used ethnographic and exploratory methods to understand the creative practices of a group of young, resource-constrained, aspiring creatives from Cape Town, South Africa, who are enrolled in design courses. This thesis explores tensions between authentic creativity and continuity, as well as notions of democratization in visual design practices. Off campus, young people predominantly appropriated mobile devices as infrastructure for creative practices. They used data frugally, grabbed media in patches and snippets, and used multiple free applications together to forge creative work, participation and distributions. These practices, which include mobile-based photography, design and branding, were situated in particular creative worlds, which revolved around distinctive visual styles. Instead of vast networks with flows of data that connect infinite nodes, these creatives experienced the web and digital media as an assemblage of technologies and tariffs for mobile data. Thus, these media-related practices were more ‘patchworked’ than networked. Once enrolled in design courses, a very different repertoire of protocols, standards, materials, technologies, concepts and ways of being became infrastructural to these young people’s participation in formal visual design practices. For many participants, an enduring distance separated them from those embodied, technical and spatial requirements for later professional participation in the design industries. These tensions demonstrated how very particular configurations of resources are infrastructural to visual design practice associated with formal industries. Infrastructure and practice are thus dynamically and asymmetrically mutually constituted. This thesis employs improvisational jamming to make the role of infrastructure visible, along with specific mobile design practices. Many of these mobile systems were standardized and encoded with cultural norms, giving creatives second-hand discourses from which to build their own creative artefacts. These case studies draw attention to the global standardization of infrastructures for creative practice, which threatens to flatten the cultural richness of local creative voices.